2023
DOI: 10.1371/journal.pone.0281754
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and attitudes of patients and healthcare workers towards the use of telemedicine in Botswana: An exploratory study

Abstract: Introduction In March 2020, the Botswana Ministry of Health and Wellness approved a National eHealth Strategy. Although a milestone, the strategy does not mention telemedicine. There is need to address this by developing an evidence-based adjunct strategy for telemedicine to facilitate its introduction and adoption. To do so, several stages of a published eHealth Strategy Development Framework were mimicked. This allowed situational awareness to be created through exploring behavioural factors and perceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…This finding was similar among HCPs involved in VCs with COPD patients [38,40,44,46,47]. Recent studies in different countries have also identified positivity in attitude from HCPs towards remote care [84][85][86].…”
Section: Behaviours and Attitudes Of Patients And Hcps Associated Dur...supporting
confidence: 57%
“…This finding was similar among HCPs involved in VCs with COPD patients [38,40,44,46,47]. Recent studies in different countries have also identified positivity in attitude from HCPs towards remote care [84][85][86].…”
Section: Behaviours and Attitudes Of Patients And Hcps Associated Dur...supporting
confidence: 57%
“…Such a strategy is necessary to redress the absence of telemedicine initiatives in the National eHealth Strategy, and the current often uncoordinated and unstructured telemedicine interventions that are difficult to scale and sustain—a situation that squanders limited national resources. Pragmatic research studies involving healthcare workers, patients and other eHealth experts clearly revealed the areas of focus that the proposed strategy should address [ 13 , 14 ]. Using this, and evidence from a variety of other sources, six priority HRIs were differentiated ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although research and pilot projects have been reported in Botswana, for example, by Ndlovu et al [ 22 ], Chavez et al [ 23 ], and Littman-Quinn et al [ 24 ], little was known about perceived telemedicine knowledge, practices, and needs of healthcare workers and patients. A recent survey and key informant-based research provided that insight [ 13 , 14 ]. Surveys of healthcare workers (HCW) and patients in three regions of Botswana had identified their perspectives on priority HRI [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations